Reflections on shading - Forsyth, D; Zisserman, A (IEEE, 1991)
It is demonstrated that mutual illumination can produce significant effects in real scenes. An example is presented to illustrate the difficulties that mutual illumination presents to shape recovery schemes. These effects are qualitatively modeled by the radiosity equation. Using the radiosity equation, the authors predict the occurrence of spectral events in the radiance, namely, discontinuities in the radiance and its derivatives. Experimental evidence establishes the validity of this approach. Mutual illumination can generate discontinuities in the derivatives of radiance unrelated to local geometry. It is argued that it is not possible to obtain veridical dense depth or normal maps from a shading analysis. However, discontinuities in radiance are tractably related to scene geometry and, moreover, can be detected.